Analisis dan Perancangan Sistem Informasi Monitoring dan Evaluasi Anggaran Pendapatan dan Belanja pada Kejaksaan Negeri Muaro Jambi - Yulandari, Restika; Purnama, Benni; Devitra, Joni (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
The Muaro Jambi District Attorney's Office in processing data for monitoring and evaluating the revenue and expenditure budget still uses the help of Microsoft Excel, there are several obstacles, namely frequent errors in the calculation of the realization of budget absorption every month and the lack of control from the Technical Implementation Officer of Activities in each field in controlling the budget that has been planned in advance, so that there are often delays in budget disbursement and reporting accuracy. The purpose of the research is to analyze and design a prototype of an information system for monitoring and evaluating revenue and expenditure budgets. The research method uses the prototype development method and the unified model language system model using usecase diagrams, activity diagrams, and class diagrams. The results of the conclusion of the system development can display staff data, division data, revenue type data, revenue budget data, expenditure type data, expenditure budget data and produce reports that can be printed according to their needs. Keywords : analysis, design, monitoring, evaluation, budget, revenue, and expenses